Answer:
1. m = -2
2. g = 7
3. y = 13
4. a = -36
5. x = 15
6. w = -18
Explanation:
1. Make the constant to the right-hand side and change its sign
a = 10 - 12
Calculate the difference a = -2
Solution
a = -2
2. Move variable to the left-hand side and change its sign
-g - 2 = - 9
Move constant to the right-hand side and change its sign
-g = -9 + 2
Calculate the sum
-g = -7
Change the signs on both sides of the equation
g = 7
Solution
g = 7
3. Divide both sides of the equation by - 7
-7y ÷ (-7) = -91 ÷(-7)
Any expression divided by itself equals 1
y = 91 ÷ (-7)
Divide two negatives equals a positive: (-) ÷(-)=(+)
y = 91 ÷ 7
Calculate the quotient
y = 13
Solution
y = 13
4. Multiply both sides of the equation by 9
9 x a/9 = 9 x (-4)
Reduce the number with the greatest common factor 9
a = 9 x (-4)
Multiply a positive and a negative equals a negative: (+)x(-)=(-)
a = -9 x 4
Multiply the numbers
a = -36
Solution
a = -36
5. Multiply both sides of the equation by 3/2
3/2 × 2/3x = 3/2 × 10
Reduce the numbers with the greatest common factor 3
1/2 × 2x = 3/2 × 10
Reduce the numbers with the greatest common factor 2
x = 3/2 × 10
Reduce the numbers with the greatest common factor 2
x = 3 x 5
Multiply the numbers
x = 15
Solution
x = 15
6. Multiply both sides of the equation by 9/4
9/4 x 4/9w = 9/4 x (-8)
Reduce the numbers with the greatest common factor 9
1/4 x 4w = 9/4 x (-8)
Reduce the numbers with the greatest common factor 4
w = 9/4 x (-8)
multiplying a positive and a negative equals and negative: (+)x(-)=(-)
w = -9/4 x 8
Reduce the numbers with the greatest common factor 4
w = -9 x 2
Multiply the numbers
w = -18
Solution
w = -18